‘LEXIMO AI’ IN DAILY ENGLISH CONVERSATION: ISLAMIC BOARDING SCHOOL STUDENTS’ PERCEPTIONS - Mashalani, Fahima; Rahman Hz, Benni Ichsanda (Jurnal Smart, 2025)
This study explores the use of Leximo AI, an AI-powered English conversation tool, by students at an Islamic boarding school with limited English exposure. Using a qualitative case study involving questionnaires and interviews with 20 male students aged 12–20, findings reveal that Leximo AI is perceived as user-friendly and effective in improving vocabulary and speaking skills. However, concerns include overreliance on the app and reduced teacher interaction. Students emphasized the continued importance of classroom learning. The study concludes that Leximo AI can complement traditional instruction, supporting technology integration in religious education under teacher guidance.